Acquired Resistance to Crizotinib in NSCLC withMETExon 14 Skipping. Issue 8 (August 2016) - Heist, Rebecca S.; Sequist, Lecia V.; Borger, Darrell; Gainor, Justin F.; Arellano, Ronald S.; Le, Long P.; Dias‐Santagata, Dora; Clark, Jeffrey W.; Engelman, Jeffrey A.; Shaw, Alice T.; Iafrate, John A.
ABSTRACT : Introduction: : MET proto‐oncogene, receptor tyrosine kinase gene ( MET ) exon 14 skipping is a targetable alteration in lung cancer. Treatment with MET proto‐oncogene, receptor tyrosine kinase inhibitor can cause dramatic responses in patients whose cancers have MET exon 14 skipping. Little is known, however, about acquired resistance in patients with MET exon 14 skipping. Methods: : Biopsy specimens obtained at baseline and at the time of progression for a patient being treated with crizotinib were compared using targeted next‐generation sequencing to assess for mechanisms of resistance. Results: : An acquired mutation in the MET kinase domain, D1228N, was found at time of progression on crizotinib in a patient with MET exon 14 skipping. Conclusions: : One potential mechanism of acquired resistance to crizotinib in patients with MET exon 14 skipping is through second‐site mutations in the MET gene. Understanding mechanisms of resistance will be important in optimizing therapy in these patients.